(untitled) - Manahan, Stanley E. (Boca Raton, 2010)
What makes this book so enduring? Completely revised, this ninth edition retains the organizational structure that has made past editions so popular with students and professors while updating coverage of principles, tools, and techniques to provide fundamental understanding of environmental chemistry and its applications. It includes end-of chapter questions and problems, and a solutions manual is available upon qualifying course adoptions. Rather than immediately discussing specific environmental problems, Manahan systematically develops the concept of environmental chemistry so that when he covers specific pollutions problems the background necessary to understand the problem has already been developed.
Phân tích và đánh giá hóa lý nước,Hóa môi trường
Keywords: Environmental chemistry